Membangun Keinovasian UMKM Melalui Peningkatan Peran Orientasi Pasar, Kompetensi SDM Dan Organisasi Pembelajaran - Dewi Kurniawati; Sri Widyastuti; Laili Savitri Noor (Fakultas Ekonomi Dan Bisnis Universitas Pancasila, 2017)
The purpose of this study is to find empirical evidence about the effect of market orientation variables, human resource competencies, and learning organizations of SMES business in Depok City on SMES innovation. This research was conducted on 100 respondents from SMES business in Depok. This research uses quantitative approach and data processing using SPSS. The results of this study indicate a significant influence of market orientation, human resource competence, and learning organizations on the innovation of SMES. These three variables simultaneously affect the innovation of SMES in Depok City. The competence of Human Resources and Learning Organization are more influencing SMES business to innovate their products compared to market orientation variable.